Faktor-Faktor yang Mempengaruhi Investasi pada Perusahaan Asuransi Jiwa Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) - Monica Aprelia Dewi; Zubaidah Nasution; Surya Setiawan (Universitas Islam Lamongan, 2021)
Abstract: This research analyzes the effect of tabarru fund and underwriting on investment in sharia life insurance companies in Indonesia that are registered in the Financial Services Authority (OJK). The independent variables are tabarru fund and underwriting. The dependent variable is an investment. The research was conducted using ten companies that met the sample selection criteria of seven years from 2013-2019. The seventy total data are registered with the financial services authority. This research used the purposive sampling technique. The data were analyzed through SPSS as a tool. This study indicated that the tabarru fund had a significant effect on investment in Islamic life insurance companies. Partial analysis (t-test) of tabarru fund had a significant positive impact on investment in Islamic insurance companies for the 2013-2019 period. The simultaneous F significance test results for the tabarru fund and underwriting F significant variables were simultaneously 0.000 less than the 0.05 significance level. Thus it can be concluded that H0 was rejected and H1 was accepted so that the regression model tested was fit, and the independent variable (tabarru fund and underwriting) simultaneously had affected the dependent variable (investment).